1982
DOI: 10.1093/bja/54.8.819
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology in Anaesthesia Iii: Mortality Risk in Patients With Coexisting Physical Disease

Abstract: The Cardiff Anaesthetic Record System has been used to examine the hospital mortality rates and relative risks for patients having anaesthesia who have certain preoperative conditions coexisting with their disease requiring surgery. Each preoperative condition was associated with a higher mortality rate than occurred in patients with no preoperative condition (for example ischaemic heart disease 7%, diabetes 5.7%, no preoperative condition 0.5%). Mortality was greater for emergency than for elective operations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(40 citation statements)
references
References 9 publications
1
35
0
3
Order By: Relevance
“…In ASA grade 4 patients the threshold was found between the CRI score II and III (4.4% mortality vs. 7.3%). Although the most frequent cause of peri-operative mortality is reported to be cardiac complications [1,2,4,14,15,19], the CRI group alone did not predict perioperative mortality as well as the ASA grade. The CRI has been evaluated prospectively in patients undergoing abdominal aortic surgery [10,11] and noncardiac surgery [13].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In ASA grade 4 patients the threshold was found between the CRI score II and III (4.4% mortality vs. 7.3%). Although the most frequent cause of peri-operative mortality is reported to be cardiac complications [1,2,4,14,15,19], the CRI group alone did not predict perioperative mortality as well as the ASA grade. The CRI has been evaluated prospectively in patients undergoing abdominal aortic surgery [10,11] and noncardiac surgery [13].…”
Section: Discussionmentioning
confidence: 79%
“…Anaesthetists have taken a leading role in identifying predictors of peri-operative mortality. In 1941 the American Society of Anesthesiologists published a physical status classification for surgical procedures (ASA grade) which has been used world-wide since that time [1][2][3][4][5][6][7]. According to its definition ASA grade is not primarily a risk predictor although it has often been advocated as such.…”
mentioning
confidence: 99%
“…Our data are therefore in agreement with the two-hit theory of MOSD and, thus, reinforce the importance of investigating acute-phase proteins or cytokines during the perioperative period in patients who will undergo major operations. [3][4][5][6][7][8]17,23,26 Patients who are candidates for major operations on the abdominal cavity deserve attention because various factors, including previous bacterial infections, malnutrition and malignancies, for instance, may primarily trigger an immune system response. 23 Patients who are more prone to complications are also more reactive to operative trauma than o thers with a normal immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the identifi cation of variables of interest for predicting the risk of postoperative infections has become the main objective of several reports. [3][4][5][6][7][8] Assessment of nutritional status and immune response may have prognostic value for such patients. It has been demonstrated that prior sensitization of the immune system may result in an inappropriate response to injury or infection.…”
Section: Introductionmentioning
confidence: 99%
“…Com relação à mortalidade cirúrgica pós-operatória diretamente relacionada às condições médicas do paciente, um estudo envolvendo uma coorte de 108 878 pacientes demonstrou uma taxa de mortalidade total de 2,2%, que variou em relação às doenças coexistentes como doenças isquêmicas do coração (7%), insuficiência cardíaca (15,8%), diabetes (5,7%), (Fowkes, Lunn et al 1982) .…”
Section: Resultsunclassified